Budaya Bermukim Orang Melayu di Kota Pontianak Terhadap Pemanfaatan Rumah di Bantaran Sungai Kapuas: Studi Kawasan Permukiman di Kelurahan Tambelan Sampit - Zain, Zairin; Aqsa, Ariq; Sunandi, Rizky (Arsir, 2022)
Vernacular architecture is the result of the work of many ethnic groups in Indonesia which was built by the local community based on the culture of living which has been carried out for generations. These traditions are part of the culture they created to facilitate daily activities and are physically implemented as spaces and traditional architectural forms in residential homes. The architecture of the houses of the Malay community in the city of Pontianak has a space and form that gives it its own characteristics. This study was conducted on houses on the banks of the Kapuas river in the Tambelan Sampit sub-district, Pontianak. This research was conducted with a case study approach to discuss the culture of the Malay community living on the banks of the Kapuas river in utilizing the environmental conditions to live in this location. The object of the study is a Malay vernacular house on the banks of the Kapuas River in the Tambelan Sampit Village area of Pontianak which is currently still inhabited. As a result, knowing the dynamics of the meaning of traditional Malay houses carried out with an interpretive approach, comprehensively, intact and interrelated (holistic).